INOVASI PEMBELAJARAN DI NAHDLATUL WATHAN (STUDI PADA MADRASAH ALIYAH KEAGAMAAN HAMZANWADI II NW ANJANI) - Muhtamin, Muhtamin; Ulya, Zihniatul; Fahrurrozi, Fahrurrozi; Zainudin, Zainudin (Dharmas Education Journal (DE_Journal), 2023)
This study aims to examine learning innovations carried out at the Hamzanwadi II NW Anjani Religious Madrasah Aliyah which is part of Nahdlatul Wathan. Nahdlatul Wathan is an Islamic organization that has a network of educational and religious institutions in Indonesia. Madrasah Aliyah Keagamaan Hamzanwadi II NW Anjani is one of the educational institutions under the auspices of Nahdlatul Wathan which focuses on religious education for upper secondary level students. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation studies. The collected data were nalyse using descriptive methods to describe and nalyse learning innovations carried out at the Hamzanwadi II NW Anjani Religious Aliyah Aliyah. One of these innovations is the use of technology in the learning process, such as the use of multimedia and interactive learning support software. In addition, there are also innovations in learning methods, such as learning-based learning approaches, assessments, and discussions between students to increase student involvement in the learning process. II NW Anjani. The results of this research are expected to provide input for the development of more effective and relevant learning in similar educational institutions, as well as provide insights for education stakeholders in facing challenges and opportunities in the current digital era.